A chromosome-scale reference genome of grasspea (Lathyrus sativus) - Vigouroux, Marielle; Novák, Petr; Oliveira, Ludmila Cristina; Santos, Carmen; Cheema, Jitender; Wouters, Roland H M; Paajanen, Pirita; Vickers, Martin; Koblížková, Andrea; Vaz Patto, Maria Carlota; Macas, Jiří; Steuernagel, Burkhard; et al. (Scientific data, 2024)
Grasspea (Lathyrus sativus L.) is an underutilised but promising legume crop with tolerance to a wide range of abiotic and biotic stress factors, and potential for climate-resilient agriculture. Despite a long history and wide geographical distribution of cultivation, only limited breeding resources are available. This paper reports a 5.96 Gbp genome assembly of grasspea genotype LS007, of which 5.03 Gbp is scaffolded into 7 pseudo-chromosomes. The assembly has a BUSCO completeness score of 99.1% and is annotated with 31719 gene models and repeat elements. This represents the most contiguous and accurate assembly of the grasspea genome to date.
Keywords: Lathyrus; Genome, Plant; chromozomy rostlin; Chromosomes, Plant; genom rostlinný